2019
DOI: 10.1021/acs.analchem.9b03550
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Magnetic Resonance Sensing via Enzyme-Mediated Click Chemistry and Magnetic Separation

Abstract: Magnetic resonance sensing (MRS) assays with simple pretreatment have drawn increasing attention for the development of biosensors, whereas conventional MRS is not competent for analyzing trace targets due to its relative low sensitivity. In this work, we employ alkaline phosphatase-mediated click chemistry as a signal transformation and amplification technique that effectively enhances the magnetic signal for amplified MRS. We outline two strategies by modulating either the aggregation state or the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Copper­(I)-catalyzed azide–alkyne cycloaddition (CuAAC) as a revolutionary biorthogonal click chemistry reaction has been extensively applied in biochemical assays due to its merits of high reaction speed, mild reaction conditions, good selectivity, and high efficiency. To date, the enzyme-like click catalysis mediated by copper nanoparticles (CuNPs) has been successfully integrated with the CuAAC click reaction for developing various CuAAC-based assays, such as fluorescence assays, magnetic resonance sensing (MRS) assays, colorimetric assays, SERS immunoassays, and electro-click assays . However, the reported solid CuO NPs used in the catalytic click reactions suffer from a high diffusion barrier, resulting in limited catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Copper­(I)-catalyzed azide–alkyne cycloaddition (CuAAC) as a revolutionary biorthogonal click chemistry reaction has been extensively applied in biochemical assays due to its merits of high reaction speed, mild reaction conditions, good selectivity, and high efficiency. To date, the enzyme-like click catalysis mediated by copper nanoparticles (CuNPs) has been successfully integrated with the CuAAC click reaction for developing various CuAAC-based assays, such as fluorescence assays, magnetic resonance sensing (MRS) assays, colorimetric assays, SERS immunoassays, and electro-click assays . However, the reported solid CuO NPs used in the catalytic click reactions suffer from a high diffusion barrier, resulting in limited catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…14 A magnetic relaxation switching (MRS) sensor was recently developed based on the "spin−spin" relaxation time (T 2 ) change of water protons originating from the state change of magnetic nanoparticles (dispersion or aggregation). 15 The MRS sensor can detect the target in the opaque samples with one step, and it is not limited by multiple washing steps or light-based interference. 16 However, it is difficult to detect small molecules by conventional MRS owing to their limited binding sites, which cannot significantly change the state of MNPs and generate a strong relaxation signal.…”
Section: Introductionmentioning
confidence: 99%
“…A magnetic relaxation switching (MRS) sensor was recently developed based on the “spin–spin” relaxation time ( T 2 ) change of water protons originating from the state change of magnetic nanoparticles (dispersion or aggregation) . The MRS sensor can detect the target in the opaque samples with one step, and it is not limited by multiple washing steps or light-based interference .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jiang et al designed a naked-eye readable plasma nanosensor using ALP-triggered agglomeration of gold nanoparticles and demonstrated its potential in immunoassay applications . Applying the ALP-labeled antibody to the immune sandwich structure and employing the same mechanism, Wu and co-workers established a magnetic resonance sensing-based immunoassay platform for the detection of small molecules . Early studies indicated that the cyclization reaction between the specially designed 5′-azide and 3′-alkyne tagged padlock probes through CuAAC can produce a relatively long single-stranded DNA (ssDNA), which nearly has the same capability as a normal ssDNA and has been used to trigger hyperbranched rolling circle amplification (HRCA) and produce large amounts of double-stranded DNAs (dsDNAs) with high efficiency .…”
mentioning
confidence: 99%
“…20 platform for the detection of small molecules. 21 Early studies indicated that the cyclization reaction between the specially designed 5′-azide and 3′-alkyne tagged padlock probes through CuAAC can produce a relatively long single-stranded DNA (ssDNA), which nearly has the same capability as a normal ssDNA and has been used to trigger hyperbranched rolling circle amplification (HRCA) and produce large amounts of double-stranded DNAs (dsDNAs) with high efficiency. 22 Since the addition of SYBR Green I in a dsDNA solution can produce enhanced fluorescence, this had been applied to develop a highly sensitive fluorescence biosensor for inorganic pyrophosphatase detection.…”
mentioning
confidence: 99%